Design solutions for U.P. faculty and staff housing units in the middle income group - Sta. Maria Oda I. (1995.)
Realizing the need for additional housing units for U.P. employees, the University allocated P54 million from U.P. funds in 1992 for the construction of walk-up apartments in its main campus at Diliman. An additional amount of P131 million was loaned from the PAG-IBIG for the completion of its P185 million housing project (Abueva, 1993). Today, these walk-up apartment units in the Hardin ng Roses and Hardin ng Dona Aurora, to name two, are leased to U.P. employees on a first-come. first-serve basis. As of December 1994, more than 500 have applied for a housing unit. Of the 1,166 U.P. housing units, only full time, regular personnel are entitled to housing privileges (Clotario & de Castro, 1995). To the fortunate employees who were awarded these housing units, the problem of space design is posed; especially since most of them belong to founding and expanding families in the middle income group. Two size types have been designated to Hardin ng Rosas- as type A with floor area of 94.5 square meters and type B, with only 54 square meters. However, Hardin ng Dona Aurora are of type B only.Specifically, the study aimed to obtain the solutions to design problems encountered in small walk-up units such as in the area of study. Survey data were obtained from the population of the 2 walk-up areas in U.P. Dliman campus. A questionnaire was distributed to the 2 sets of respondents to elicit information on their characteristics and perceptions regarding their present living quarters. From the results, comments and recommendations for the improvement of the interior environment were also obtained. The Descriptive Research Method was employed in this study and the Component Method for residential design was partly used to analyze data. the U.P. Faculty and Staff housing unit owner's job related characteristics were as follows: half of the respondents were 26-35 years old and over half of the respondents were female. 70% were college graduates while 30% have obtained post-graduate units or degrees. The job profile shows that 40% of the respondents worked as U.P. staff, 30% as instructors and 30% as professors. 40% of the faculty respondents have 3-10 years work experience in the University while 20% have worked for U.P. for more than 15 years. @0 % of the staff respondents have 3-10 years work experience and another 20% for more than 15 years. The U.P. Faculty's annual basic salary ranges from P54,000 to 92,000 (60%) while the U.P. Staff earn from P52,000 to P72,000 annually. 90% received benefits which were monetary in nature while the remaining 10% claimed to have none. The respondents' interior design perceptions of the apartment units were measured in terms of the importance they attached to the interior design factors and the rank they assigned to criteria for a better interior environment as related to the household. The factor of space called for individuality of each functional area of the unit in that, combined functional areas were not favored at all. The need for the living room to be most spacious ranked first. Storage space were most highly called for in the kitchen and dining areas, with the preference for the built-in type. The identified factors needing improvement were flooring and storage system. Budget constraints, high maintenance requirements and unavailability of interior design advising were 3 of the major hindrances of the U.P. housing unit owners consider as they make these their homes until the next year to 10 more and even later. The distinct status definition in the area is supported by the fact that the respondents belong to the U.P. work force who earn between P4,300 to P7,600 a month. The U.P. employees are in general agreement as to the increasing need for government housing projects within the campus. This has been indicated by a large number of wait-listed applicants for university housing units. Distinct design solutions for U.P. housing units under study were given based on their household needs. Recommendations which evolved from the findings of the study include the following: 1. More emphasis on the development of sheltering provision and design program involving research relevant to the field of design in the Philippines. 2. Extending interior design services to the Filipino masses particularly, in this case, to the middle income group in order to address the problem of unavailability of such services being a major hindrance to keeping an aesthetically and functionally sound apartment. 3. Developing and continuing with further research the area of study and specifically those which involve designing small spaces and its relevance in the future Philippine housing.
Research paper (ID 199)--University of the Philippines Diliman.
Keywords: Interior decoration -- Philippines